OPTIMALISASI KOMUNIKASI ORGANISASI DALAM MENINGKATKAN KINERJA APARATUR SIPIL NEGARA (ASN) BIDANG BINA KONSTRUKSI DINAS PEKERJAAN UMUM DAN TATA RUANG PROVINSI SULAWESI SELATAN - Husnia , Husnia; Zelfia, Zelfia; Rabiah , Sitti (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
The purpose of this study was to examine the optimization of communication at the Department of Public Works and Spatial Planning of South Sulawesi Province. The research was conducted in the city of Makassar, South Sulawesi. Department of Public Works and Spatial Planning Jl. Andi Prince Pettrani No. 90 South Sulawesi Province. This study used a qualitative descriptive method, with eight (6) informants in this study. Data collection techniques were through observation, interviews and documentation. Data analysis was carried out by collecting data, reducing, presenting data and drawing conclusions.The results of this study indicate that the Organizational Communication Optimization of the Department of Public Works and Spatial Planning of South Sulawesi province. Optimization is an action to optimize or achieve maximum results in a government agency or organization. Optimization in an organization is very important where to achieve the target an organization must pay attention and carry out its task functions properly.